Flora sporovykh rasteniĭ SSSR. - Akademii͡a nauk SSSR. Botanicheskiĭ institut (Leningrad : Izd-vo Akademii nauk SSSR, 1952)
Erratum slip inserted.
Added t.p. in Latin
At head of title, v. 1- :Akademii͡a nauk SSSR. Botanicheskiĭ institut.
Includes bibliographies.
Mode of access: Internet.
Keywords: Botany -- Soviet Union; Cryptogams